Diagnosis of Subtype 2B von Willebrand Disease in a Patient with 2A Phenotype of Plasma von Willebrand Factor - Gaucher, Christine; de Romeuf, Christophe; Rauïs-Morret, Michéle; Corazza, Francis; Fondu, Pierre; Mazurier, Claudine (Thrombosis and Haemostasis, 1995)
Type 2A of von Willebrand disease refers to qualitative variants with decreased platelet dependent function that is associated with the absence of high molecular weight forms of von Willebrand factor (vWF) multimers. Type 2B refers to qualitative variants with increased affinity for platelet glycoprotein lb. In this report we describe the study of a patient who has been previously diagnosed as having subtype 2A von Willebrand disease (vWD), because she had no heightened ristocetin-induced platelet aggregation, no large and intermediate molecular weight von Willebrand factor (vWF) multimers in plasma, and no increase in plasma vWF capacity to bind to normal platelets in the presence of low ristocetin concentrations. The DNA sequencing of the 3’ part of the exon 28 of the vWF gene where most of the subtype 2A mutations have already been identified, did not detect any nucleotide change. At variance, a G to A transition changing the encoded amino acid residue from Val 553 to Met in mature vWF, was found in the 5’ part of this exon. This mutation which has already been found in several unrelated families with 2B vWD and the increased binding of the patient platelet vWF on normal platelets in the presence of low ristocetin concentrations provide evidence for subtype 2B vWD. This study thus illustrates the importance of the molecular characterization of patients in the correct diagnosis and classification of type 2 vWD.